Study on quality parameters of wine at opening and deterioration with time - Pathak, Arvind; Regmi, Arma; Gautam, Kalpana; Wagle, Manoj Nidhi (Scientific World, 2023)
Wine is an alcoholic beverage made from grapes containing alcohol ranging from 5-15% by volume. Wine consumption in the Nepalese market is gaining steady growth in recent years. In this study, parameters such as specific gravity, total acidity, pH, percentage of alcohol content, amount of total dissolved solid, presence of furfural, methyl alcohol and heavy metal were selected for analysis of red and white wine with time after the opening of the packet wine at the time interval of 15, 20 and 25 days respectively. An increase in acidity and specific gravity (0.9780-0.9992 g/mL) while decrease in alcohol content (9.54%-8.03% by volume), presence of heavy Iron and Copper found below 0.003 and absence of furfural and methyl alcohol were observed with time. Consumption of wine in controlled amounts could prevent heart disease and circulatory problem. However, excess wine consumption can inhibit new brain cell development and depressive disorders.